THE INFLUENCE OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODEL ON THE READING SKILLS OF FOURTH-GRADE STUDENTS OF NU SLEMAN PRIMARY SCHOOL - Fathimatuzzahroh, Fathimatuzzahroh; Amaruddin, Hidar (PROGRES PENDIDIKAN, 2024)
This research aims to determine the effect of the Cooperative Integrated Reading Composition (CIRC) learning model on the intensive reading skills of fourth-grade students at SD NU Sleman. This research uses quantitative methods, with a quasi-experimental design in the form of a nonequivalent control group design, with an experimental and control class. With two variables, the independent variable is the CIRC learning model, and the dependent variable is intensive reading skills. The population used was 74 fourth-grade students at SD NU Sleman and a sample size of 15 in each experimental and control class. The instruments used in this research were multiple-choice tests and observation. Hypothesis testing uses the independent sample t-test. The research results showed a significant difference in intensive reading skills between the experimental class, which used the CIRC learning model, and the control class, which did not use the CIRC learning model. Classes that use the CIRC learning model have a higher average post-test score with an average difference of 12.67. The significance of the difference in intensive reading skills can be seen in the Sig value obtained. (2-tailed) is 0.000, which means it is smaller than 0.05. So, there is an influence of the CIRC learning model on the intensive reading skills of fourth-grade students at SD NU Sleman.